2006
DOI: 10.1532/ijh97.05182
|View full text |Cite
|
Sign up to set email alerts
|

Loss of O 6 -Methylguanine-DNA Methyltransferase Protein Expression Is a Favorable Prognostic Marker in Diffuse Large B-Cell Lymphoma

Abstract: Although aberrant promoter hypermethylation of O6-methylguanine-DNA methyltransferase (MGMT) is a favorable prognostic marker in patients with diffuse large B-cell lymphoma (DLBCL), MGMT protein expression has not been thoroughly examined. The aim of this study was to evaluate the clinical implication of MGMT protein expression and its correlation with promoter hypermethylation of the gene. We investigated MGMT protein expression by immunohistochemical analysis of 63 DLBCL patients who received cyclophosphamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
5
23
1
Order By: Relevance
“…Furthermore, Al-Kuraya et al determined that their frequency of GCB profile DLBCL (13%) was somewhat lower than described in previous studies. They also found a much higher rate of MGMT methylation in their patients (75.9%) as compared with previous studies [1,3,30,31,46,47]. In our study, no significant association was found between MGMT promoter methylation status and the expression levels of apoptosis-related proteins, the AI and the PI.…”
Section: Türk Et Al Apoptosis Proliferation In Large B-cell Lymphomacontrasting
confidence: 66%
See 3 more Smart Citations
“…Furthermore, Al-Kuraya et al determined that their frequency of GCB profile DLBCL (13%) was somewhat lower than described in previous studies. They also found a much higher rate of MGMT methylation in their patients (75.9%) as compared with previous studies [1,3,30,31,46,47]. In our study, no significant association was found between MGMT promoter methylation status and the expression levels of apoptosis-related proteins, the AI and the PI.…”
Section: Türk Et Al Apoptosis Proliferation In Large B-cell Lymphomacontrasting
confidence: 66%
“…MGMT methylation was reported at a frequency from 36% to 52% in Western populations in previous studies [1,3,30,46,47]. Higher rates (75.9%) were found in Middle Eastern populations [38].…”
Section: Türk Et Al Apoptosis Proliferation In Large B-cell Lymphomamentioning
confidence: 97%
See 2 more Smart Citations
“…126 In addition to predicting drug response, MGMT promoter methylation is an independent predictor of better outcome in glioblastoma and diffuse large B-cell lymphoma. 124,127 …”
Section: Predicting Response To Chemotherapy: Mgmt Profiling In Gliobmentioning
confidence: 99%